PENGUATAN PERAN POSYANDU DALAM MENINGKATKAN KETAHANAN MASYARAKAT TERHADAP BENCANA TSUNAMI DI WILAYAH PESISIR KOTA BANDA ACEH MENGGUNAKAN PENDEKATAN KNOWLEDGE MANAGEMENT - Eka Sartika; Khairul Munadi; Endang Mutiawati (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The lack of disaster knowledge is one of the causes of the high casualties of women in the tsunami in Banda Aceh. Strengthening the posyandu's role in improving community resilience to disasters is essential. Research’s purpose is to identify posyandu role, strengthen posyandu role by analyzing the factors that become supporter and challenge faced by posyandu, and to initiate effective efforts in building disaster resilient community through Knowledge Management(KM) approach. The research uses quantitative and qualitative approach. Determination of sample by purposive involving 6 Posyandu located in coastal area of Banda Aceh City. Data were collected with questionnaires, in-depth interviews and focus group discussions. Analysis technique used is thematic analysis method. The results revealed that 77.8% of Posyandu managers have disaster knowledge at the medium level. Posyandu has many supporting factors to act as the agent of disaster knowledge dissemination. Strengthening the posyandu's role needs to be realized by continuous KM approach, its strategy is to make the program regularly disseminate disaster knowledge, build Posyandu community network with non-formal learning facilities so that it can give input to policy and program in achieving development sustainable in Banda Aceh.Key words : Tsunami, Posyandu, and Knowledge Management